PENGORGANISASIAN FORUM WARGA SEBAGAI STRATEGI MEMPERKUAT PARTISIPASI PEREMPUAN DALAM PELAKSANAAN UNDANG-UNDANG DESA - Trustisari, Hastin (Istek Widuri Jakarta, 2018)
A mandate Law of Village Number 6, 2014 Article 82 clearly to set how important citizen participation in the governance of village. Its article has opportunities and challenges, because of citizen participation opened widely except for women to convey of aspiration, advice, and opinion by writing and verbally in development village. This research conducted from June to December 2017 at Jalatunda Village, Mandiraja Subdistrict, Bajarnegara District, Central Java Province. This research has found that public participation for women in the decision process in the development of village is the most important but difficult to be implemented. It is influenced by some factors such as domination of local leader (man), underestimates of the role of women and less of knowledge related women in the development of the village. Purpose of this research is to get information how to the organizing of Citizens Forum could be a strategy to enforce women participation in the development of village so that implemented of governance of village which involving women in participation in social justice. The results of this research showed that Citizens Forum is part strategic to organized become social transaction to develop citizen capacity mainly for women to be involved be subject in village development process. The conclusion of this research is that Citizens Forum the function should maximize, not only as gathering Citizens Forum but also for education arena and transfer knowledge for women in order to get opportunity to take role, to speak in public, and able to deliver aspiration and need as citizen who has right and opportunity in development their village.